PATRIOTISM in the Lithuanian Language - Smetona, Marius (Vilnius University Open Series, 2021)
Patriotism as a phenomenon is not new and it has manifested itself in various ways. The roots of contemporary Lithuanian patriotism go back to the middle of the 19th century and the beginning of the 20th century. The available data from that period do not allow making any specific conclusions but it can be seen that the word patriotism was a relatively new in the beginning of the 20th c. Patriotism was best understood in the interim period between the two world wars, when an attitude started to form that own nation should not only be elevated distinguishing it from others but it is also something everybody has to be proud of. After Lithuania was incorporated into the Soviet Union, a new concept, i. e. soviet patriotism, emerged. This idea is based on internationalism, commitment to socialist order and solidarity of soviet nations. The attitude of a present-day Lithuanian to patriotism is reflected best in contemporary discourse. The issues of love for Homeland have been frequently discussed not only by political analysts or historians but also by representatives of arts and sports. Moreover, the media have frequently discussed issues, which are not characteristic of real patriotisms or even have raised some doubts about patriotism being an exaggerated phenomenon. However, comprehensive research studies on patriotism are few. The concept of patriotism has almost escaped the research focus of linguists. Therefore, an attempt will be made to bridge the gap in linguistic research analysing the data available in dictionaries, discourses and surveys.It can be stated that a contemporary individual tends to nurture the same values as people in the interim period. These embraces work for the sake of homeland and nation, concern about its future and welfare, nurturance of homeland and the mother tongue, culture and history. Loyalty, gratefulness, nostalgia to homeland, attachment to the land of their birth, honesty, courage, freedom, responsibility and pride are assigned to patriotism. Patriotism implies defence of own country in the hour of peril. This is particularly emphasised in the historical discourse, where defence of own country is one of the prevailing motives, and in the surveys of students. Contemporary discourse allocates less attention to this issue. Patriotism is related to acknowledgement of the country’s mistakes, promoting its name and celebration of public holidays.Patriotism can hardly be imagined without knowledge of the national history, culture, its heroes and prominent figures. The data from both discourses and surveys allow claiming that patriotism is perceived as a feeling or feelings, an inner state or a value. In fact, it can be stated that though patriotism is not an old concept, which replaced such concepts as ethnicity and love for homeland, the view of patriotism, which formed at the end of the 19th c. and in the beginning of the 20th c., has remained the same up to now.
Keywords: patriotism; ethnicity; concept; ethno-linguistics